Mis-splicing-derived neoantigens and cognate TCRs in splicing factor mutant leukemias - Kim, Won Jun; Crosse, Edie I; De Neef, Emma; Etxeberria, Inaki; Sabio, Erich Y; Wang, Eric; Bewersdorf, Jan Philipp; Lin, Kuan-Ting; Lu, Sydney X; Belleville, Andrea; Fox, Nina; Castro, Cynthia; et al. (Cell, 2025)
Mutations in RNA splicing factors are prevalent across cancers and generate recurrently mis-spliced mRNA isoforms. Here, we identified a series of bona fide neoantigens translated from highly stereotyped splicing alterations promoted by neomorphic, leukemia-associated somatic splicing machinery mutations. We utilized feature-barcoded peptide-major histocompatibility complex (MHC) dextramers to isolate neoantigen-reactive T cell receptors (TCRs) from healthy donors, patients with active myeloid malignancy, and following curative allogeneic stem cell transplant. Neoantigen-reactive CD8 T cells were present in the blood of patients with active cancer and had a distinct phenotype from virus-reactive T cells with evidence of impaired cytotoxic function. T cells engineered with TCRs recognizing SRSF2 mutant-induced neoantigens arising from mis-splicing events in CLK3 and RHOT2 resulted in specific recognition and cytotoxicity of SRSF2-mutant leukemia. These data identify recurrent RNA mis-splicing events as sources of actionable public neoantigens in myeloid leukemias and provide proof of concept for genetically redirecting T cells to recognize these targets.